Wykorzystanie rachunku kosztów jakości w zarządzaniu procesowym - Ciechan-Kujawa, Marlena (Quality Costs Accounting in Process Management, 2005)
This paper describes principal issues in management of the costs, which are connected with the assurance quality and failure quality of products and processes. The author presents the methods of the quality costs management. The accent is put on the necessity of the quality costs management in strategic and operating areas.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 160-169